Monetary Policy Trade-offs and the Correlation between Nominal Interest Rates and Real Output - Fuhrer, Jeffrey C.; Moore, George R. (American Economic Review, 1995)
We present a structural model of the U.S. economy that combines our price-contracting specification with a term-structure relationship, an aggregate demand curve, and a monetary-policy reaction function. The model matches important features of postwar data well and provides a structural explanation of the correlation between real output and the short-term nominal rate of interest. We perform a battery of monetary-policy experiments which show that, as viewed through the lens of this model, monetary policy has struck a good balance recently among competing monetary-policy objectives.